Resistivitas Batuan Berdasarkan Metode Geolistrik Konfigurasi Schlumberger untuk Menentukan Potensi Air Tanah Sebagai Acuan Sumur Bor - Fadilah Fadilah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to analyze rock resistivity based on the geoelectric method of the Schlumberger configuration to determine the potential for groundwater as a reference for boreholes. The method used in this research is the geoelectric resistivity method with a Schlumberger configuration. Data acquisition modeling was analyzed using Progress Version 3.0 to describe the subsurface based on measurement sounding points in the field. The main targets for these measurements are confined aquifer traps and sandstone stratigraphy. Field measurement points are at coordinates S 030 43 '52.2